Coping strategies in learning literature : a survey of UNIMAS tesl and esl students - Lau, Phek Hung (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study aimed at finding out UNIMAS TESL and ESL undergraduates’ perceptions of learning literature, the difficulties that that the undergraduates experience in literature learning and the coping strategies that they use to overcome the problems that they encountered in learning the literature. The participants of this study were 74 Universiti Malaysia Sarawak students who are taking the education course. For the purpose of this study, two instruments were used for data collection. Questionnaire was used as the primary instrument and it was distributed to all the 74 undergraduates. Interview was used as the secondary instrument and only 15 of them were selected to take part in the interview sessions. Percentage and frequency count was used in analyzing the data. The overall findings illustrated that most of the undergraduates like to study literature although some of them are not fond of studying literature. The results demonstrated that the students experienced many difficulties in learning the literature and they used many coping strategies to cope with the difficulties encountered in learning the literature.